An Updated Review of Macro, Micro, and Nanostructured Hydrogels for Biomedical and Pharmaceutical Applications - Caroline S. A. de Lima; Tatiana S. Balogh; Justine P. R. O. Varca; Gustavo H. C. Varca; Ademar B. Lugão; Luis A. Camacho-Cruz; Emilio Bucio; Slawomir S. Kadlubowski (MDPI AG, 2020)
Hydrogels are materials with wide applications in several fields, including the biomedical and pharmaceutical industries. Their properties such as the capacity of absorbing great amounts of aqueous solutions without losing shape and mechanical properties, as well as loading drugs of different nature, including hydrophobic ones and biomolecules, give an idea of their versatility and promising demand. As they have been explored in a great number of studies for years, many routes of synthesis have been developed, especially for chemical/permanent hydrogels. In the same way, stimuli-responsive hydrogels, also known as intelligent materials, have been explored too, enhancing the regulation of properties such as targeting and drug release. By controlling the particle size, hydrogel on the micro- and nanoscale have been studied likewise and have increased, even more, the possibilities for applications of the so-called XXI century materials. In this paper, we aimed to produce an overview of the recent studies concerning methods of synthesis, biomedical, and pharmaceutical applications of macro-, micro, and nanogels.